Developing Students’ Spatial Imagination In Steam Education - Sofiboyeva, Gulchehra (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article discusses STEAM educational technologies and their use, the significance of using STEAM educational technologies in developing spatial imagination of primary school students as well as defines several definitions of the concept of imagination, and methods for developing students' spatial imagination.